Evaluasi dan Pengembangan Layanan Sistem Informasi PPID Dinas Kesehatan Provinsi Jawa Timur Dengan Menggunakan Standar dan Teknis Kemanan Sistem Pemerintahan Berbasis Elektronik (SPBE) - Dwianggoro, Benedictus Radyan; Narulita, Luvia Friska (Yayasan Nuraini Ibrahim Mandiri, 2024)
The Indonesian government's steadfast commitment to increasing efficiency and transparency is clearly visible in the Republic of Indonesia Presidential Decree Number 95 of 2018 concerning Electronic-Based Government Systems (SPBE). In line with this commitment, this research focuses on evaluating and improving Information System Services from PPID Information Services at the East Java Health Office, adopting SPBE security standards. The main goal is to use the Prototyping method and follow the guidelines provided by the SPBE Technical Standards and Security Procedures, implemented through the Laravel framework. The research process begins with problem analysis using observation and interview techniques. The literature review provides important insights for the development of PPID information systems. Service evaluation is carried out to produce recommendations for improvement. The implementation phase combines the Prototyping method with indicators derived from SPBE technical standards and security procedures. System testing, including the application of the Penetration Testing method, identified 9 vulnerabilities in the website, with 2 at the medium risk level and 7 at the low risk level. While progress in complying with security standards is satisfactory, recommendations for continued development of OWASP ZAP are critical. The main objective is to make a positive contribution to the effectiveness, integration, sustainability, efficiency, accountability, interoperability and security of PPID Information System Services at the East Java Health Office. This effort is in line with the principles of transparency and efficiency in governance.